The time-varying prognostic value of stenosis and plaque burden in coronary artery disease - Jukema, Ruurt A.; Maaniitty, Teemu; Nurmohamed, Nick S.; Raijmakers, Pieter G.; Hoek, Roel; Driessen, Roel S.; Planken, R. Nils; Twisk, Jos; van der Harst; Pim; Cramer, Maarten J.; Saraste, Antti; et al. (Oxford University Press (OUP), 2026)
Aims
Conflicting results have been reported on the prognostic value of coronary stenosis grade and plaque burden. We aimed to investigate the time-varying risk for cardiovascular events associated with diameter stenosis (DS%) and plaque burden.
Methods and results
Patients without a documented cardiac history who underwent coronary computed tomography angiography for suspected coronary artery disease were included. The most severe DS% and plaque burden, defined as percentage atheroma volume (PAV), were used for analysis. The primary endpoint was a composite of all-cause mortality and non-fatal myocardial infarction. For analysis, the maximal follow-up time was 8 years. Among 2819 patients [mean age 62 ± 10; 1245 (45%) male], 235 events occurred during a median follow-up of 6.9 years. Cox models including cardiovascular risk factors, DS%, and PAV demonstrated that DS% but not PAV was predictive for short-term events at 1-year follow-up [adjusted hazard ratio (aHR) 1.028, 95% confidence interval (CI) 1.013–1.044 vs. 1.015, 95% CI 0.978–1.053]. In contrast, PAV but not DS% was predictive for long-term events at 8-year follow-up (aHR 1.035, 95% CI 1.021–1.050 vs. 1.005, 95% CI 0.999–1.012). The predictive value of DS% was stronger before than after 1 year of follow-up (aHR <1 year 1.027, 95% CI 1.012–1.042 vs. aHR 1–8 years 1.001, 95% CI 0.994–1.008; P < 0.01 for difference), while the predictive value of PAV did not significantly change (P = 0.12).
Conclusion
Coronary diameter stenosis holds the highest prognostic significance for short-term cardiovascular events, while plaque burden predicts events in the long term.